Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Thiên Lê
2611
18 tháng 5 2022 lúc 13:13

`a)` Thay `m=-1` vào `(1)` có:

    `x^2-2(-1+3)x+2.(-1)-1=0`

`<=>x^2-4x-3=0`

`<=>(x-2)^2=7`

`<=>|x-2|=\sqrt{7}`

`<=>x=2+-\sqrt{7}`

Vậy với `m=-1` thì `S={2+-\sqrt{7}}`

______________________________________________________

`b)` Ptr có:`\Delta'=[-(m+3)]^2-(2m-1)=m^2+4m+4+6=(m+2)^2+6 > 0 AA m`

    `=>\Delta' > 0 AA m`

`=>` Ptr luôn có `2` nghiệm pb `AA m`

________________________________________________________

`c)AA m` áp dụng Vi-ét có:`{(x_1+x_2=[-b]/a=2m+6),(x_1.x_2=c/a=2m-1):}`

Ta có:`x_1 ^2+x_2 ^2=13`

`<=>(x_1+x_2)^2-2x_1.x_2=13`

`<=>(2m+6)^2-2(2m-1)=13`

`<=>4m^2+24m+36-4m+2-13=0`

`<=>4m^2+20m+25=0`

`<=>(2m+5)^2=0`

`<=>m=[-5]/2` 


Các câu hỏi tương tự
Xuân Thường Đặng
Xem chi tiết
Thảo Thảo
Xem chi tiết
Nguyên
Xem chi tiết
Đỗ Thành Đạt
Xem chi tiết
Pham Trong Bach
Xem chi tiết
gh
Xem chi tiết
LovE _ Khánh Ly_ LovE
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Trần Thủy Tiên
Xem chi tiết